PERANAN KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PENCURIAN DENGAN KEKERASAN BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2002 TENTANG KEPOLISIAN DI WILAYAH HUKUM KEPOLISIAN RESOR KAMPAR - Suprayogi '; Mukhlis R; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The phenomenon of rising crime rates criminal acts of theft with violence incoming and handled by the Police Kampar lately demanded hard work in performing the duty of every police officer personnel by promoting and sustaining the law above everything, including orders from superiors. This is useful for creating a professional police force that has, dedication, ability and sufficient knowledge and in performing their duties. The phenomenon of rising crime rates criminal acts of theft with violence incoming and handled by the Police Kampar lately demanded hard work in performing the duty of every police officer personnel by promoting and sustaining the law above everything, including orders from superiors. This is useful for creating a professional police force that has, dedication, ability and sufficient knowledge and in performing their duties.